A Analysis of Students' Reading Interest in the Library of MAN 3 Jombang - Mohammad Faridl Darmawan; Khusnul Rahmawati (APPLICATION: Applied science in Learning Research, 2021)
The research entitled "Analysis of Student Reading Interest in the Library of MAN 3 Jombang" contains the interest in reading, factors supporting and inhibiting reading interest, as well as the librarian's efforts to increase student interest in reading at MAN 3 Jombang. In this study using a qualitative descriptive research method with data collection techniques in the form of interview questionnaires and documentation. This study aims to determine; 1) reading interest of students at MAN 3 Jombang,2) supporting factors and inhibiting students' reading interest, 3), efforts that can be made to increase reading interest. The results obtained in this study are that the students' reading interest in the library of MAN 3 Jombang is very good. The librarian of MAN 3 Jombang has made efforts to increase reading interest very well.